APPLICATION OF GUIDED INQUIRY LEARNING MODELS TO IMPROVE STUDENTS 'SOCIAL STUDIES LEARNING OUTCOMES CLASS IVA SDN 07 JATI MULYA - Tukiman (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
Based on the description of the table above, of the 28 grade IVA students of SDN 07 Jati Mulya (18 male students and 8 female students) who did not reach the minimum completeness criteria were 21 people, namely around 45% where classically they did not meet the completeness criteria set by the school 75%. Thus there are still many students who have not reached the minimum completeness criteria. So that the teacher has to repeat the same material over and over again for several meetings in an effort to improve student learning outcomes. This makes the demands of the curriculum not achieved because the time allocation that should be used for the next material is used to discuss the same material. Seeing this condition, the researcher considers it necessary to provide a learning model that can arouse students in learning. One learning model that leads to student curiosity and improves student learning outcomes is the guided inkuri learning model. Guided inkuri learning model is a learning activity that emphasizes the process of thinking critically and analytically to find and discover for themselves the problem that is being questioned to students. Social studies learning with inquiry is able to lead students to realize what they have obtained after learning. As for the formulation of the problem in this study is